Influence of SiO2 on electrical properties of the highly nonlinear ZnO-Bi2O3-MnO2 varistors. Issue 13 (October 2017) - Bai, Hairui; Li, Miaomiao; Xu, Zhijun; Chu, Ruiqing; Hao, Jigong; Li, Huaiyong; Chen, Chong; Li, Guorong
Abstract: The ZnO-Bi2 O3 -MnO2 - x SiO2 (ZBMS) varistor was prepared at a low sintering temperature of 880 °C via the conventional solid state method. The phase transformation, microstructure, and electrical properties of the ZBMS varistor were studied as a function of doping amount of SiO2 . It is showed that the growth of ZnO grain is restrained by the introducing of SiO2 ; and the grain size decreases from 4.68 μm to 2.98 μm. The breakdown voltage E 1mA exhibits a simultaneous variation from 608.11 V/mm to 1232.88 V/mm. It is also revealed that SiO2 has a significant effect on the Schottky barrier structure. As a result, the highest barrier height φ b of 5.34 eV is attained at a composition of x  = 2.0 wt%, which contributes to the highest nonlinear coefficient α of 73.68. Moreover, all the samples show low leakage current of I L  <  0.1 μA.